Optimization of Health Service Facilities Through Intelligence Artificial Viewed from the Legal Perspective of Positivism - Abidin Fikri; Zainal Arifin Hoesein (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. The use of Artificial Intelligence (AI) in Indonesia's healthcare sector presents an innovative solution to address challenges such as limited healthcare facilities and a shortage of medical personnel. In line with Article 4, Paragraph (1), letter c of Law No. 17 of 2023, every individual has the right to receive safe, quality, and affordable healthcare services. For AI to be successfully integrated into healthcare, it must align with legal principles based on positivism, with clear regulations to ensure accountability, security, and the quality of services provided. Purpose. This study aims to analyze the role of AI in optimizing healthcare facilities and improving the performance of medical personnel in Indonesia, while also exploring the legal challenges that arise in the use of AI in healthcare from the perspective of positivist law. Method. This research adopts a normative juridical approach, utilizing both a legislative approach and an analytical approach. The study examines relevant legal frameworks and regulations, analyzing how AI is incorporated into healthcare and the legal issues surrounding its use. Results. The study finds that AI plays a significant role in improving the efficiency of healthcare facilities and the performance of medical personnel in Indonesia. AI enhances diagnostic speed, reduces workloads, and improves service quality, especially in regions with a shortage of medical personnel. However, the study also identifies significant legal challenges, including issues related to accountability, patient data protection, and technical standards. Currently, the regulations governing these aspects are inadequate. Conclusion. AI has significant potential to optimize healthcare facilities and improve medical personnel performance in Indonesia. However, from the perspective of positivist law, clear and comprehensive regulations are necessary to address challenges related to accountability, data protection, and technology security. These regulations are crucial to ensure legal certainty and protection for all stakeholders involved in the healthcare system.